Personal data privacy and protection in a surveillance era : technologies and practices - Akrivopoulou, Christina; Psygkas, Athanasios (Hershey, PA : Information Science Reference, 2011)
'This book spans a number of interdependent and emerging topics in the area of legal protection of privacy and technology and explores the new threats that cyberspace poses to the privacy of individuals, as well as the threats that surveillance technologies generate in public spaces and in digital communication'--Provided by publisher.
Includes bibliographical references (p. 329-361) and index.
Keywords: Data protection -- Law and legislation -- United States; Electronic surveillance -- Law and legislation -- United States; Privacy, Right of -- United States; Records -- Access control -- United States; Digital communications -- United States